Palliative and end-of-life care for adults with advanced chronic obstructive pulmonary disease: a rapid review focusing on patient and family caregiver perspectives. Issue 4 (December 2017) - Mathews, Gillian; Johnston, Bridget
Abstract : Purpose of review: The aim of the review was to explore patient and family caregiver perspectives on key issues for ensuring quality of end-of-life care for people with chronic obstructive pulmonary disease (COPD). The growing evidence on the value of specialist palliative care services demonstrates significant improvements in treatments and provisions; however, much of the literature is generic in nature or centred on people with a cancer diagnosis. In this review, we examine the literature to ascertain the views and needs of patients and carers affected by advanced COPD, a highly debilitating condition that can have a profoundly negative impact on the quality of end-of-life experience. Recent findings: A total of 19 papers were included in the review. The main themes in the literature were Holistic Care, Illness Trajectory and Technology. Summary: Areas of unmet need emphasized across physical, psychosocial and spiritual domains were identified, particularly in relation to appropriate and timely conversations. Positive developments in the care and treatment of advanced COPD include the use of the STIOLTO Respimat inhaler, a brief educative and psychosocial intervention based on cognitive-behavioural therapy, and high-intensity exercise training. There is some evidence regarding the use of technology in end-stage COPD. Abstract : Supplemental Digital Content is available in the text